Effects of hydraulic structures on fish passage: an evaluation of 2D vs 3D hydraulic analysis methods - Ryan, Erin R., author; Bledsoe, Brian P., advisor; Myrick, Christopher A., committee member; Nelson, Peter A., committee member (Colorado State University. Libraries, 2015)
Channel-spanning hydraulic structures can act as barriers to upstream fish movement. Negative consequences associated with this disruption of longitudinal habitat connectivity highlight the need for accurate and practicable assessment techniques. Three-dimensional evaluation methods have been shown to resolve the complex flow at in-stream structures and accurately predict fish movement; yet three-dimensional modeling can be impractical due to time and resource requirements. This study investigates using a two-dimensional computational fluid dynamics model and statistical analyses to describe the hydraulic conditions at a whitewater park structure in Lyons, Colorado. Fish movement observations are paired with the resulting hydraulic variables along spatially explicit, continuous paths which represent potential swimming routes. Logistic regression analyses indicate that flow depth and velocity are strongly associated with fish passage; a combined depth and velocity variable accurately predicts 92% of rainbow trout (Oncorhynchus mykiss) and brown trout (Salmo trutta) movement observations at this hydraulic structure. The results of this study suggest that two-dimensional analysis methods can provide a cost-effective approach to assessing the effects of similar hydraulic structures on fish passage when three-dimensional analysis in not feasible. Further, conclusions from this study can be used to guide management and design decisions for both trout and fishes with comparatively lower swimming performance.
Keywords: fish passage; hydraulic structure; barrier; whitewater park; hydraulic modeling